Peran Perpustakaan Sekolah Sebagai Sumber Belajar Siswa di SDN Bagus 2 Marabahan: The Role of the School Library as a Learning Resource for Students at SDN Bagus 2 Marabahan - Irni Cahyani; Syaiful Rahman; Lastaria Lastaria (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aims to describe the implementation and obstacles in the role of the library as a learning resource at SDN Bagus 2 Marabahan.This research is a qualitative descriptive study. The informants of this research are school principals, administrators, teachers and students. Data collection techniques used are observation, interviews, and documentation. Data analysis uses the steps of data collection, data presentation, and drawing conclusions. Data validity testing techniques using triangulation, reference materials, and member checks. The results of the research show that the implementation of library management as a learning resource has not run optimally. Some aspects of library management still have many shortcomings, such as buildings that do not meet the requirements, equipment and supplies that are not yet complete, collections of library materials are still small, services are still not supervised, and there is no clear library code of conduct. Obstacles to the library as a source of learning are inadequate building or room facilities, limited book collections, incomplete tools and equipment, and the limited quota of assistance provided by the government through the education office.